Dynamics of immune - antioxidant status in patients with hypothyroidism on the background transcranial electrostimulation - E. I. Dydyshko; O. S. Okhremenko; V. D. Levichkin (Кубанский научный медицинский вестник, 2014)
The study involved 30 patients (25 females, 5 males) aged 34 to 55 years with a confirmed diagnosis of hypothyroidism, mean age 43,5 years, disease duration ranged from 1 year to 15 years (study group). TSH ranged from 5,15-99,27 mME/L (27,26±4,20 mME/L). In the blood of patients found to decrease the activity of catalase 2-2,5 times (p